Uranium Contents in Wheat Samples of Saudi Arabia - A.F. Al-Dayel, Omar (Asian Journal of Chemistry, 2010)
Wheat is one of the most grown crops in most of the world countries. Radionuclides may be concentrated in environment in a manner that can pose risk to human health. Accurate knowledge of such radionuclides in human food is of great importance to avoid any risk. In this work. Inductively coupled plasma mass spectrometry (ICP-MS) and α-spectrometry techniques were applied to determination of uranium in wheat samples. Wheat samples were collected from ten regions through Saudi Arabia. Also bran and white flour samples were investigated.